2016
DOI: 10.1007/s00405-016-3894-8
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of horizontal semicircular canal canalolithiasis and cupulopathy using bow and lean test and head-roll test

Abstract: Accurate lateralization is important to improve treatment outcomes in horizontal semicircular canal (HSCC) benign paroxysmal positional vertigo (BPPV). To determine the involved side in HSCC-BPPV, the intensity of nystagmus has been compared in a head-roll test (HRT) and the direction of nystagmus was evaluated in a bow and lean test (BLT). The aim of this study is to compare the results of a BLT with those of a HRT for lateralization of HSCC-canalolithiasis and cupulopathy (heavy cupula and light cupula), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 20 publications
1
24
1
Order By: Relevance
“…To examine bowing and leaning nystagmus, the patients were subjected to bowing (90°) and leaning (45°) in a sitting position. The direction of bowing nystagmus corresponded to the affected side while that of leaning nystagmus was opposite to the affected side, which was consistent with previous observations [2,8,9,11].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To examine bowing and leaning nystagmus, the patients were subjected to bowing (90°) and leaning (45°) in a sitting position. The direction of bowing nystagmus corresponded to the affected side while that of leaning nystagmus was opposite to the affected side, which was consistent with previous observations [2,8,9,11].…”
Section: Resultssupporting
confidence: 92%
“…The diagnostic criteria for light cupula were the presence of persistent geotropic DCPN, which lasted for more than 2 minutes in a supine head-roll test, and the presence of a null plane where nystagmus disappeared with slight head rotation either to the right or to left. Determination of the affected side was made based on identification of a null plane, i.e., the side of a null plane corresponds to the affected side [2,8,9].…”
Section: Methodsmentioning
confidence: 99%
“…[ 8 ] Moreover, because not only PSN but also leaning or lying-down nystagmus is not observed in all patients with HSCC canalolithiasis, [ 10 , 21 , 22 ] comparative interpretation of the results of a supine roll test, bow and lean test, and PSN would be essential in determining the affected side in HSCC canalolithiasis. [ 10 , 11 ] In our study, a caloric test was performed in 12 patients with PSN, which revealed no canal paresis in all patients. The fact that only 39% (12 of 31) of patients with PSN took a caloric test may impose limitation on the validity of this study because caloric weakness might have been superimposed on HSCC BPPV causing spontaneous nystagmus, even though clinical tests including head impulse test revealed no signs suggesting unilateral vestibulopathy.…”
Section: Discussionmentioning
confidence: 76%
“…The pathologic ear can be identified by applying the Ewald's second law: the quick phases of the most intense nystagmus point to the affected side ( Pérez-Vázquez et al., 2017 , von Brevern et al., 2015 ); but, many times it is difficult to recognize the stronger nystagmus. The bow and lean manoeuvre ( Choung et al., 2006 , Kim et al., 2016 , Lee et al., 2010 ; von Brevern et al, 2015 ; Yetiser and Ince, 2015 ) may be very useful and, in case of cupulolithiasis, the pseudospontaneous nystagmus ( Asprella-Libonati, 2014 , Asprella-Libonati, 2008 , von Brevern et al., 2015 ) can also help to identify the pathologic side.…”
Section: Treatment Of the Horizontal Canal Bppvsmentioning
confidence: 99%